Preterm infant born after in vitro fertilization: case report - Druzhinina N.A; Panova L.D; D.R. Merzlyakova; Shiryaeva G.P (LCC «Medicine-Inform», 2019)
Preterm infant born after in vitro fertilization: case report N.A. Druzhinina, L.D. Panova, D.R. Merzlyakova, G.P. Shiryaeva Bashkir State Medical University, Ufa, Russian Federation Recent studies demonstrate that children born after in vitro fertilization (IVF) are at higher risks of various unfavorable conditions including low Apgar scores, complications of neonatal adaptation, and intraventricular hemorrhage, a disorder specific for preterm children. The results are greater hospital stay and further hospital admissions. Factors provoking these complications are still controversial. Among them are medications and methods for infertility, or reproductive system disorders accompanying pregnancy after IVF. It is still disputable whether health impairments in children result from mothers' extragenital and gynecological comorbidities or IVF itself. The paper addresses clinical case illustrating management strategy of a preterm infant born after IVF considering the issues of extreme morphological and functional immaturity. Preterm infant management and providing favorable conditions for their feeding considering corrected age are the primary task for pediatricians. Knowing of the specifics of growth and development of preterm infants is of particular importance in daily clinical practice. Keywords: children health, assisted reproductive treatment, IVF, prematurity, extremely low birth weight. For citation: Druzhinina N.A., Panova L.D., Merzlyakova D.R., Shiryaeva G.P. Preterm infant born after in vitro fertilization: case report. Russian Journal of Woman and Child Health. 2019;2(2):151-154.